1992
DOI: 10.1002/jso.2930490406
|View full text |Cite
|
Sign up to set email alerts
|

The effect of indomethacin on acute radiation induced gastrointestinal injury: A morphologic study

Abstract: Radiation-induced intestinal injury is a dose limiting factor in the treatment of pelvic, abdominal, and retroperitoneal malignancies with radiation therapy. In experimental models, radiation has been associated with increased intestinal prostaglandin activity and in clinical trials prostaglandin inhibitors have been demonstrated to improve the symptoms of acute radiation enteritis. This study was conducted to determine if the prostaglandin inhibitor indomethacin could prevent the morphologic changes of acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In experimental models, radiation has been associated with an increase in intestinal prostaglandin activity, and in clinical trials, prostaglandin inhibitors have been shown to improve the symptoms of acute radiation enteritis [14]. This study was conducted to evaluate COX-2 expression in acute and late stages of radiation-induced intestinal injury, and to investigate the possible protective effect of the selective COX-2 inhibitor, Rofecoxib, against radiation-induced intestinal injury in rats.…”
Section: Introductionmentioning
confidence: 99%
“…In experimental models, radiation has been associated with an increase in intestinal prostaglandin activity, and in clinical trials, prostaglandin inhibitors have been shown to improve the symptoms of acute radiation enteritis [14]. This study was conducted to evaluate COX-2 expression in acute and late stages of radiation-induced intestinal injury, and to investigate the possible protective effect of the selective COX-2 inhibitor, Rofecoxib, against radiation-induced intestinal injury in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory responses after irradiation have been shown in other tissues and organs. Interstitial inflammation involving polymorphonuclear leukocytes was observed by histological examination of irradiated intestinal tissues (20,21). Pneumonitis was observed 2 to 6 months after lung irradiation with doses of 8 Gy (22).…”
Section: Discussionmentioning
confidence: 99%
“…However, administration of sodium salicylate and indometacin together decreased the beneficial effects of indometacin. Rose et al (1992) reported reduced polymorphonuclear leucocyte infiltration and decreased tissue degeneration in indometacintreated rats after 50 Gy (single dose) of whole-abdomen irradiation.…”
Section: Non-steroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 96%